The Sage handbook of political communication - Semetko, Holli A.; Scammell, Margaret (Sage, 2012)
This handbook provides a review of the major research associated with political communication and sets the agenda for future study in this important discipline. It explores influences on political communication such as the media and technology and looks at the influences on political communication research.